Defining toxicity in multiplayer online games: A systematic literature review - Kordyaka, Bastian; Karaosmanoglu, Sukran; Laato, Samuli (Elsevier BV, 2026)
Driven by the technological advances of recent years and the opportunity to interact in real-time with others worldwide, toxicity in multiplayer games emerged as a major issue impacting players' well-being and the eSports industry-a lose-lose situation. Despite its urgency, there remains a lack of consensus on the definition of toxicity. To address this, we conducted a systematic literature review (N =853), identifying 32 articles in human-computer interaction databases. Analyzing the identified articles using inductive content analysis, we present (i) a complex picture of various toxicity conceptualizations in the existing literature, (ii) a unifying multidimensional definition for toxicity, (iii) a demonstration of the definition's application as a sequential process relating to widely encountered acts of toxicity, and (iv) recommendations for future research on toxicity, particularly in the growing domain of eSports. Specifically, we provide the following definition for toxicity in multiplayer online games: "A collective term for acts that are perceived as disruptive by other players that do not occur as a requirement of gameplay that can take different (a) forms of interaction (text and/or speech and/or behavior), (b) targets (teammates and/or opponents), (c) intentions (external and/or internal), and (d) timing (action and/or reaction)."